Regional Computable General Equilibrium Models for Denmark: Three papers laying the foundation for regional CGE models with agglomeration characteristics - Lars Brømsøe Termansen (Copenhagen Business School (CBS), 2008)
The paper analyses the effects of introducing taxes and regional transfers on the equilibrium properties in a standard Core-Periphery model. A central government levies taxes on production factors and redistributes the revenue to all agents regardless of their location. In the case of Core-Periphery economy this is in effect a re-allocation of agglomeration rents. Simulations show that taxes and transfers alter the Core-Periphery model's properties by moving the Break and Sustain points. The range of freeness of trade with Core-Periphery outcomes is reduced for transfers to the periphery, and increased for transfers to the core. The width of the overlap where the models exhibit hysteresis effects remains the same regardless of the transfers. The analysis reveals that in the Core-Periphery outcome the agglomeration rents can be taxed without exhausting the core's scale effects. The tax revenues can then be redistributed such that periphery regions and the central government have incentives in promoting core regions, which function as industrial locomotives for the whole economy.
hdl:10398/7739
Keywords: 650; modeller; skatter; regionaløkonomi; generel ligevægtsteori